Resposta do feijoeiro a fungos endofíticos - Hayashibara, Carolina Alessandra de Almeida (2017)
Endophytic fungi are microorganisms that live a part of their life in a host, no causing apparent damage. These fungi have been used for different purposes, such as biological control of pathogens, as producers of volatile organic compounds and promoters of plant growth. Thus, aim of this work was to evaluate effect of 12 endophytic isolates belonging to the genus Acremonium, Muscodor and Simplicillium on the development of two common bean cultivars (BRSMG Madrepérola and BRSMG União). For fungi inoculation, cultivars seeds were placed in Petri dishes in contact with fungi radicle emission. Subsequently, seeds were sown in pots and kept in greenhouse until harvest. Cultivars seeds inoculated were used as controls. Two experiments were carried out in greenhouse, in factorial scheme 13x2, with 12 endophytic fungi and control and two common bean cultivars. Experiments were conducted in a randomized complete block design with three replicates. Evaluated traits were: plant height (AP), root length (CR), leaf index (IF), number of days for flowering (NDF), number of pods per plant (X), number of grains per pod (Y), mass of 100 grains (Z) and yield (W). From the obtained results, it was observed that there was a significant difference for the characteristics evaluated in two seasons, and yield was of greater magnitude in first season. In the analysis of joint variance and the Dunnett's test, it was observed that endophytic fungi Acremonium sp. (C20), M. vitigenus (C19) and Simplicillium sp. (C18), when inoculated in cultivars, provided an increase in grain yield by up to 48% compared to control, are showing promise in increasing bean productivity.